Penyuluhan Pengelolaan dan Pembuatan Sampah Organik Menjadi Pupuk Kompos - Septi Ardianty; Andri Purnama Sari; Putri Febriyanti Kusman; Fatatun Malika; Feno Suci Wulandari; Febrina Sari Putri; Tiara Oktapiani; Tiara Tiara; Yeni Ariyanti; Santi Lestari; Nanda Williansyah (Journal of Community Development, 2024)
The living environment is a unity of space and all objects, forces, conditions and living creatures, including humans and their behavior. Waste in Indonesia has an unresolved problem, as the population increases, the amount of waste produced by human activities also increases, so education is needed for the public. Education is any planned effort to influence other people, whether individuals, groups or society, so that they do what is expected by educational practitioners. In relation to waste management education for the community, it is hoped that the public will know about waste management using the 3R approach, namely reduce, reuse, recycle, in this case the most emphasized is waste management by composting. This community service is carried out to increase public knowledge regarding waste management by reducing, reusing, recycling. This community service uses pre-test and post-test methods, also using education and demonstrations about waste management. The results obtained from this community service were that the community experienced an increase in knowledge after being given health education and demonstrations about waste management. Those who were given the education looked very enthusiastic and had a high level of curiosity because the people who were given the education provided feedback, namely by answering questions from the community service team and the community also learned about how to manage waste by composting it. Based on the results of outreach activities to the community about how to manage waste and the dangers of burning waste by burning it as well as a demonstration of making organic waste into compost, public knowledge has increased